Marine Diatom Skeletonema costatum Dietary Supplementation Improves Growth, Immunological Responses, Antioxidant Activities, Gene Expressions, and Digestive Enzymes of Shrimp Litopenaeus vannamei - Mohamed Ashour; Einar Ringø; Mohamed M. Mabrouk; Ahmed I. A. Mansour; Mohammed A. E. Naiel; Abdallah Tageldein Mansour; Rabee M. A. Gheetas; Ehab Mohamed; Ahmed F. Abdelhamid (Aquaculture Nutrition)
This work highlighted the impact of dry concentrations (0, 1, 2, and 4 g/kg diet) of the marine diatom species Skeletonema costatum (SK0%, SK0.1%, SK0.2%, and SK0.4%, respectively) as an aquafeed additive on the postlarvae of Pacific whiteleg shrimp (Litopenaeus vannamei). During an 8-week feeding trial, the impact of S. costatum on growth, digestive enzymes, antioxidant activities, immunity-associated gene expressions, and immunological responses of Pacific white shrimp was investigated. The protein, lipid, and carbohydrates of S. costatum were 33.50%, 35.95%, and 11.87%, respectively. Shrimp reared in group SK0.4% exhibited a significant improvement in growth performance indicators, compared to the other groups. The results showed that, compared to the control group (SK0%), shrimp-fed S. costatum supplemented groups (SK0.1%, SK0.2%, and SK0.4%) showed significantly (p <0.05) higher amylase activities. Compared to the control group (SK0%), shrimp-fed S. costatum groups (SK0.1%, SK0.2%, and SK0.4%) demonstrated major significant (p<0.05) improvement in catalase and superoxide dismutase values. Shrimp reared in group SK0.4% showed a significant (p<0.05) improvement in lipase and lysozyme activities. The increasing levels of S. costatum dietary supplementation significantly (p<0.05) increase the relative gene expression of the p53-like protein isoform delta (p53) gene. SK0.4% revealed a major significant (p<0.05) increase in the relative gene expression of the prophenoloxidase (PPO1) and peroxiredoxin (Prx) genes. This study highlights the potential of S. costatum as a promising aquafeed additive enhancing growth performance and immunity of Pacific whiteleg shrimp health, opening the way for more sustainable shrimp aquaculture practices.